Remarkable preservation of microbial mats in Neoproterozoic siliciclastic settings: Implications for Ediacaran taphonomic models - Callow, R; Brasier, M (2009)
It is beyond doubt that the appearance of infaunal bioturbation and metazoan biomineralization across the Ediacaran-Cambrian transition irreversibly affected the nature of marine sediment architecture and biogeochemistry. Here we review those changes in relation to their likely effect upon the processes of fossil preservation, especially within siliciclastic sediments. Processes of soft-tissue preservation in siliciclastic settings from the Ediacaran Period, including microbes and microbial mats as well as Ediacaran macrofossils, are here reviewed within this context. Highlighted examples include the exceptional preservation of microbes found in association with wrinkle structures and Ediacaran macrofossils in England and Newfoundland (replicated by silicate minerals) and in the White Sea region of Russia (replicated by iron sulphide). These occurrences show that soft-tissue preservation in siliciclastic settings went well beyond that typical for Ediacaran macrofossils alone and also extended to similar modes of preservation in associated microbes. Using these new observations it can be argued that several existing explanations for Ediacaran fossil preservation can be united within a biogeochemical model that involves evolution of the sediment mixed layer across this transition. © 2009 Elsevier B.V. All rights reserved.